IMPACT OF SEEDS SOAKING AND SEEDING DATES ON YIELD AND IT’S COMPONENTS OF SORGHUM - Shakir S. Mirare; Nihad M. Abood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A field experiment was carried out during spring and fall seasons of 2021 at the experimental field of Al-Hamidhyia research station -College of Agriculture - University of Anbar to investgate the effect of variety, soaking with atonik and seeding dates on yield and its components of sorghum. the experiment was carried out using RCBD, within split-split plots arrangement with 3 replications. The main plots included three seeding dates for spring season (15/3, 1/4 and 15/4) and three seeding dates for the fall season (1/7, 10/7 and 20/7), while sub plots included seeds soaking with three concentrations of Atonik(0, 2.5 and 5 mlL-1), whereas the sub-sub plots included three varieties of Sorghum bicolor (Inqath, Lilo and Giza 113). The results showed that the Inqath variety was significantly superior in the studied traits and gave highest grain yield (4.70 and 5.70 ton ha-1) for both seasons prodused.Soaking seeds with Atonik had a significant effect on the studied traits; the highest concentration (5 ml L-1) was significantly superior and achieved a highest grain yield (4.79 and 5.36 tons ha-1)for both seasons respectively. Seeding dates significantly affected the studied traits.